Sports supplement use in road cycling: A comparative analysis by sex and competitive category - García-Durán, J.; Romero-García, D.; Martínez-Sanz, J. M.; González-Jurado, J. A.; Sánchez-Oliver, A. J. (Sports, 2025)
This study analyzes and compares sports supplement (SS) consumption among federated road cyclists, considering sex and competition category. The aim is to identify key factors influencing SS use and provide insights for developing nutritional strategies in cycling. A cross-sectional, descriptive study was conducted, involving 1503 cyclists (1231 men and 272 women). Data were collected through a validated questionnaire assessing anthropometric data, training habits, SS consumption patterns, and sources of information. Results indicate that 64.3% of cyclists currently use SS. Women reported a significantly higher consumption rate (88.2%) compared to men (59.1%), although men had a higher average SS intake than women (8.28 ± 9.36 vs. 6.76 ± 5.96). Additionally, SS use decreased with age and competition level, with elite cyclists showing the highest prevalence (76.3%) and master 50 the lowest (58.4%). Group A supplements (scientifically supported) were the most frequently used, while Group C supplements (limited evidence) and Group D substances (prohibited) were more commonly consumed by men. Findings highlight significant differences in SS consumption based on sex and competition level, with elite cyclists and women reporting higher prevalence. However, men reported a higher average number of SS consumed. The study underscores the need for targeted nutritional education, particularly among master cyclists, to promote evidence-based SS use and minimize the risks of ineffective or unsafe supplementation. Future research should explore the long-term effects of SS consumption in cycling and the effectiveness of educational interventions for safe and optimized supplementation practices.